THE ROLE OF OCCUPATIONAL SAFETY AND HEALTH EDUCATION IN IMPROVING KNOWLEDGE AND AWARENESS OF STUDENTS AT SUMUR BATU 4 STATE ELEMENTARY SCHOOL - Isnawati; Dewi Puspaningtyas Faeni (Musytari : Neraca Manajemen, Akuntansi, dan Ekonomi, 2024)
This study aims to explore the role of Occupational Health and Safety (OHS) education in improving students' knowledge and awareness at SD Negeri Sumur Batu 4. Through a qualitative research method with a case study approach, data were collected through observations, interviews, and questionnaires with students, teachers, and school staff. The research findings indicate that OHS education has a significant impact on enhancing students' understanding of the importance of safety and health practices in the school environment. Additionally, the implementation of the OHS program successfully increased students' awareness of potential risks and prevention methods. These findings underline the importance of OHS education from an early age as a preventive effort in creating a safe and healthy learning environment, as well as equipping students with the principles of safety and health for their daily lives. This study recommends further development of OHS programs in elementary schools and ongoing training for educators to ensure long-term effectiveness.